DC-SIGN (CD209)-mediated interactions between bacteria, lung cancer tissues, and macrophages promote cancer metastasis - Qiao Li; Nihal Hasan; Fei Zhao; Ying Xue; Sizhe Zhu; Yin Lv; Ling-yu Jiang; Kun Yang; Wenjin Li; Yingmiao Zhang; Yingxia He; Huahua Cai; et al. (Infectious Agents and Cancer)
Abstract One of the hallmarks of lung cancers is the earlier metastasis resulting from the dissemination of cancer cells. Although accumulating evidence suggests that bacterial infection may be involved in the development of the metastasis of lung cancer, few studies have explored the molecular mechanisms of bacterial infection in the dissemination of lung cancer cells. A series of studies have indicated that certain Gram-negative bacteria are able to hijack antigen-presenting cells (APCs) via interaction with DC-SIGN (CD209) receptors to facilitate the dissemination of pathogens, including viruses, bacteria, fungi, and parasites. Therefore, in the present work, it was hypothesized that bacterial infection may promote the dissemination of cancer cells via the utilization of a similar mechanism. It was first discovered that human lung cancer tissues contain a very high diversity of bacterial DNAs, indicating the co-existence of lung cancer tissues and microbial organisms. It was then found that lung cancer tissues express DC-SIGN, leading to binding with a Gram-negative bacterium, Shigella sonnei. Further, this bacterium was found to be able not only to induce the expression of DC-SIGN on macrophages but also to enhance the migration ability of lung cancer cells in vitro. The in vivo experiments supported these observations, showing that in wild-type (WT) mice, Shigella sonnei infection significantly increased tumor size, weight, and metastatic nodules compared to SIGNR1 knockout (KO) mice. These observations were associated with increasing DC-SIGN expression in WT mice. Finally, these results suggest that bacterial infections could play a significant role in promoting lung cancer progression and metastasis via DC-SIGN-mediated mechanisms.